Cardiovascular complications in pregnant woman with primary mediastinal B-cell lymphoma - Inquilla Coyla, Melisa (2022)
A 26-year-old pregnant woman with 29 weeks of gestational age reported two months of cough, dyspnea, orthopnea, and palpitations. Chest tomography revealed a 10x12cm solid mass in the right lung. Echocardiography showed that the tumor compromised the right atrium and ventricle, and was diagnosed by transcutaneous biopsy as primary mediastinal B-cell lymphoma (PMCBL). The patient presented 2:1 atrial flutter, sinus bradycardia, and ectopic atrial bradycardia. Due to the rapid poor evolution, it was decided to terminate the pregnancy by cesarean section and start chemotherapy, after which the cardiovascular complications resolved. PCML is a very rare lymphoma that can affect pregnant women in any trimester, its symptoms are related to its rapid growth and compromise of the heart, causing various cardiovascular manifestations (heart failure, pericardial effusion, cardiac arrhythmias). PCMLC is characteristically chemosensitive and has a good prognosis.